1999
DOI: 10.1021/ol990231e
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Silyl Enol Ethers with Xenon Difluoride in MeCN:  Evidence for a Nonclassical Radical Cation Intermediate

Abstract: The reactions of xenon difluoride in MeCN solution in Pyrex flasks with a series of TMS enol ethers have been investigated. The types of products formed are dependent on the structures of individual enol ethers, but under these conditions all products are consistent with a mechanism involving single electron transfer to un-ionized XeF2 giving a radical cation and subsequent formation of an α-fluoroketone, together with some ketone formation. The results suggest that if the radical cation is particularly stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…They proposed a SET initiated mechanism in accord with our previous proposals that XeF 2 reacts with organic substrates via SET in MeCN solution. 9,11,12,21 Reaction of the boronic acid 12 with XeF 2 in CH 2 Cl 2 gave a dark brown fuming solution, which was shown to be a complex mixture containing a tiny amount of 4-fluorotoluene 4 (R¼F) ( 19 F NMR À119 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…They proposed a SET initiated mechanism in accord with our previous proposals that XeF 2 reacts with organic substrates via SET in MeCN solution. 9,11,12,21 Reaction of the boronic acid 12 with XeF 2 in CH 2 Cl 2 gave a dark brown fuming solution, which was shown to be a complex mixture containing a tiny amount of 4-fluorotoluene 4 (R¼F) ( 19 F NMR À119 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…The observation that syn ‐ and anti ‐3‐FMACBC were biologically as active as the parent anti ‐3‐FACBC led to the development of iodinated analogues of FMACBC where the fluoromethyl groups were replaced by iodovinyl moieties (Figure ). Thus, syn ‐ and anti ‐1‐amino‐3‐[2‐iodoethenyl]‐cyclobutane‐1‐carboxylic acids ( syn ‐3‐IVACBC ( 50 ), anti ‐3‐IVACBC ( 51 )), and 1‐amino‐3‐iodomethylene‐cyclobutane‐1‐carboxylic acid ( gem ‐3‐IVACBC ( 52 )) were prepared (Figure ) .…”
Section: Synthesis Of the Iodinated Alicyclic Amino Acidsmentioning
confidence: 99%
“…These mechanistic conclusions are supported by our studies of reactions of other substrates in which the product composition is determined by the combination of solvent and vessel. These include studies of TMS benzoates, 4 enol ethers 6 and carboxylic acids. 8 With the intention of supporting our preparative and mechanistic studies by identifying the species present in solution under organic reaction conditions, we have determined the 19 F NMR and UV spectra of xenon difluoride in various solvent/cell systems.…”
Section: -mentioning
confidence: 99%
“…1,2 In a series of studies we have shown that both solvent and reaction vessel can profoundly influence the mode of reaction of xenon difluoride with organic substrates. [3][4][5][6][7][8][9] Although the instability of xenon difluoride in glassware has been known for some time, Pyrex ® flasks have been widely used, and advocated, 2 for carrying out organic reactions but, apart from our own work, 5 the role of the glass surface in determining the reaction pathway has not been recognised. We have shown, for example, that aryltrimethylsilanes are rapidly fluorinated by xenon difluoride at room temperature (Equation 1) but only in a Pyrex ® flask.…”
Section: Introductionmentioning
confidence: 99%